2015
DOI: 10.1038/nbt.3277
|View full text |Cite
|
Sign up to set email alerts
|

Expression of trehalose-6-phosphate phosphatase in maize ears improves yield in well-watered and drought conditions

Abstract: Maize, the highest-yielding cereal crop worldwide, is particularly susceptible to drought during its 2- to 3-week flowering period. Many genetic engineering strategies for drought tolerance impinge on plant development, reduce maximum yield potential or do not translate from laboratory conditions to the field. We overexpressed a gene encoding a rice trehalose-6-phosphate phosphatase (TPP) in developing maize ears using a floral promoter. This reduced the concentration of trehalose-6-phosphate (T6P), a sugar si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
326
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(340 citation statements)
references
References 67 publications
7
326
0
7
Order By: Relevance
“…Tre6P levels were decreased by about half in the ear spikelets under both drought stressed and nonstressed conditions, while Suc was increased under nonstressed conditions. In a commentary on the work of Nuccio et al (2015), the simultaneous increase in Suc and decrease in Tre6P, presumably signaling low Suc, was considered to be puzzling (Guan and Koch, 2015). However, these reciprocal changes are exactly what would be predicted from the Suc-Tre6P nexus model, i.e.…”
Section: Tre6p and Abiotic Stress Tolerancementioning
confidence: 85%
See 2 more Smart Citations
“…Tre6P levels were decreased by about half in the ear spikelets under both drought stressed and nonstressed conditions, while Suc was increased under nonstressed conditions. In a commentary on the work of Nuccio et al (2015), the simultaneous increase in Suc and decrease in Tre6P, presumably signaling low Suc, was considered to be puzzling (Guan and Koch, 2015). However, these reciprocal changes are exactly what would be predicted from the Suc-Tre6P nexus model, i.e.…”
Section: Tre6p and Abiotic Stress Tolerancementioning
confidence: 85%
“…This landmark example of how to improve stress tolerance in a major crop species, with no yield penalty under nonstressed conditions, highlights both the potential of engineering trehalose metabolism for crop improvement and the likely need for spatio-temporally targeted interventions for a successful outcome (Nuccio et al, 2015). It also throws a spotlight on TPP.…”
Section: Tre6p and Abiotic Stress Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it has been suggested that control of KIN10/11 by [Tre6P] may prime the regulation of growth-related genes to capitalize upon increased energy availability, rather than by inducing growth directly (Nunes et al, 2013a(Nunes et al, , 2013b. Remarkably, the impact of this pathway is sufficiently global that its manipulation can increase maize (Zea mays) yields by almost 50% (Nuccio et al, 2015) and increase the yield and drought tolerance of wheat (Triticum aestivum; Griffiths et al, 2016).…”
mentioning
confidence: 99%
“…Already, spatial regulation of T6P metabolism has been shown to improve the allocation of leaf photosynthate to developing kernels of maize (Zea mays) in varied environments (Nuccio et al, 2015). Advances based on computational modeling, precision monitoring, genotype characterization, gene manipulation, and metabolic engineering will accelerate progress toward these goals.…”
Section: Closing Remarksmentioning
confidence: 99%